Answer:
4a^2-6b^2+12
Step-by-step explanation:
(a^2 - 2b^2 + 3) - (4b^2 - 5) + (3a^2 + 4)
distribute the negative sign to each term in the 2nd expression
a^2-2b^2+3-4b^2+5+3a^2+4
combine like terms
4a^2-6b^2+12
Answer: $1.75
Step-by-step explanation:
Increase 1.25 by 4.25
5.31
Presently increase 1.25 by 2.85
3.56
Take away 3.56 from 5.31
1.75
Answer:
x=17
Step-by-step explanation:
5x-35=50
+35 +35
_________
5x=85
÷5 ÷5
__________-
x=17
Hope this helps :D
And if u could pls give me brainly tysm if u do!!
Answer:
56.6m to 1.d.p
Step-by-step explanation:
circumference=2πr
=2×3.142×9
=56.556m
=56.6m to 1.d.p
Just multiply the denominator and the whole number then add the numerator
23/9
7/2
37/5
16/5
23/4
33/5
The answers are in order you put it in like 1-6
Can I have brainiest please